Effects of Varying Photoperiodic Regimens on Critical Biological Fitness Traits of Culex quinquefasciatus (Diptera: Culicidae) Mosquito Vector. (29th March 2018) - Ukubuiwe, Azubuike Christian; Olayemi, Israel Kayode; Omalu, Innocent Chukwuemeka James; Arimoro, Francis Ofurum; Baba, Bulus Musa; Ukubuiwe, Chinenye Catherine
This study investigated the effects of varying photoperiodic conditions on critical life stages' parameters of Culex quinquefasciatus . To this end, first larval stage was reared under different constant photoperiodic regimens: 0, 6 (short), 12 (equal), 13 (prevailing condition), and 18 and 24 (long) hours of light (hL). Duration of development, survivorship, emergence successes, adult longevity, caloric indices (CIs), and utilisation of teneral reserves for metamorphosis at each regimen were monitored. Analyses revealed significant negative effects of increasing photoperiod on all entomological variables measured. Short photo-phases elicited faster development times, increased life stages' survivorship and number at emergence, adult longevity, and CI for all life stages while increasing teneral components for adult life traits. The information generated in this study is important in understanding the role played by photoperiod in disease transmission and for development of integrated vector control strategies based on environmental manipulation.